If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3x + -10 = 2x + -5 Reorder the terms: -10 + 3x = 2x + -5 Reorder the terms: -10 + 3x = -5 + 2x Solving -10 + 3x = -5 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -10 + 3x + -2x = -5 + 2x + -2x Combine like terms: 3x + -2x = 1x -10 + 1x = -5 + 2x + -2x Combine like terms: 2x + -2x = 0 -10 + 1x = -5 + 0 -10 + 1x = -5 Add '10' to each side of the equation. -10 + 10 + 1x = -5 + 10 Combine like terms: -10 + 10 = 0 0 + 1x = -5 + 10 1x = -5 + 10 Combine like terms: -5 + 10 = 5 1x = 5 Divide each side by '1'. x = 5 Simplifying x = 5
| P(x)=x^3+7x^2+4x | | m^6-16m^3+64=0 | | 6x+3=6(4)+3 | | .50(6-y)=y | | -10.2x=71.4 | | 4x^2-33x+41=-9x+6 | | 6t=-46 | | 5x-9=4(x-3) | | 5p=-15 | | -9(2b+3)+(19b-3)=0 | | 7y^2-8y+15-11y^2-8y+6= | | a^2+8a=9 | | x=-11 | | -(3x+5)+1-4(x-2)+5x-2=0 | | x^2-2x+4=8x-4 | | t^2-10t-24=0 | | x^2+12x+6=0 | | 4x+3(2x-8)=8x-40 | | 4.5x-3.8y+6.9x-0.2y= | | 2s+7=10s-7 | | 27+2x+3=5x | | 2s+7=10-7 | | X^2-2x+4=-8x-4 | | 5x+63=7(x-9) | | n-7=13 | | x+2/3= | | x^2-2x=21 | | X^2-4x+5=10 | | -5(3x+7)=-15 | | 7x-9=2x+21 | | 3x-9y-8x+7y= | | x+2= |